(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
Lucio Saffaro is one of the most original artists of the last decades. Unclassifiable in any pictorial avant–garde line, he has been able to combine his various passions in a wonderful way: painting, mathematics (especially polyhedra) and poetry. There are several hundreds of studies that have been carried out on his work in which the three mentioned interests are inseparable. And yet it is still possible to write about him as a person, as an artist and as a scientist. In this text I try to make a further contribution to the knowledge of the polyhedral person from the point of view of his whole field humanism, using not only the description of his work in the three different fields, but also revealing some implications of his profound humanity.